Pengaturan Perdagangan Bursa Karbon Di Indonesia Serta Perbandingan Pengaturan Perdagangan Bursa Karbon Dengan New Zealand - Tutun Zalsal Bella (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Indonesia, which previously traded carbon through a voluntary market mechanism, has switched its carbon trading implementation through a carbon exchange (IDX Carbon) since September 26, 2023. This means that carbon trading in Indonesia is carried out through the Indonesia Stock Exchange (IDX), and all carbon units are traded as securities or securities, whereas previously carbon transactions in Indonesia were voluntary. The implementation of carbon trading is a form of Indonesia's commitment to implementing the Paris Agreement and the Kyoto Protocol in reducing Greenhouse Gas emissions by 29% in 2030 with its own capabilities and up to 41% with international support. In the implementation of carbon trading in Indonesia, it is carried out through a mandatory market and the Indonesia Stock Exchange has been appointed as the institution organizing carbon trading, but the regulations that form the basis for the implementation of carbon trading do not clearly regulate how to determine carbon prices, the institution authorized to issue Technical Approval for Upper Emission Limits for Business Actors (PTBAE-PU) and Greenhouse Gas Emission Reduction Certificates as units traded on the Carbon Exchange.